2022
DOI: 10.3389/fpsyg.2022.865680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immediacy of Feedback on Continuous Intentions to Use Online Learning From the Student Perspective

Abstract: The immediacy of feedback in media is emerging to enhance the interactivity of online experience for users. There is a gap in the study to explore the impacts of the immediacy of feedback on continuous intentions to use online learning from the student perspective. This study aims to fill the gap to investigate the impacts of the immediacy of feedback on students’ continuous intentions to use online learning. This study utilizes the technology acceptance model (TAM) and expectation theory model (ETM) to concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Table 4 presents the studies on the efficacy of online learning, indicating advantages and disadvantages [41]. Some studies found that it negatively affected student motivation and engagement [80], while others found that it improved the students' interest and engagement [74]. These findings are summarised in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 presents the studies on the efficacy of online learning, indicating advantages and disadvantages [41]. Some studies found that it negatively affected student motivation and engagement [80], while others found that it improved the students' interest and engagement [74]. These findings are summarised in Table 4.…”
Section: Resultsmentioning
confidence: 99%